2015
DOI: 10.4049/jimmunol.1401320
|View full text |Cite
|
Sign up to set email alerts
|

CCR2-Dependent Dendritic Cell Accumulation in the Central Nervous System during Early Effector Experimental Autoimmune Encephalomyelitis Is Essential for Effector T Cell Restimulation In Situ and Disease Progression

Abstract: Dendritic cells (DCs)—while absent from the healthy CNS parenchyma—rapidly accumulate within brain and spinal cord tissue during neuroinflammation associated with experimental autoimmune encephalomyelitis (EAE, a mouse model of multiple sclerosis). Yet, while DCs have been appreciated for their role in initiating adaptive immune responses in peripheral lymphoid organ tissues, how DCs infiltrate the CNS and contribute to ongoing neuroinflammation in situ is poorly understood. Here we report that; 1) CD11c+ bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 60 publications
15
43
0
Order By: Relevance
“…However, similar to MS, RR-EAE is also characterized by extensive CNS perivascular infiltration of inflammatory APCs that perpetuate damage (3, 8, 43). In particular, iDCs are major players in CNS autoimmune pathology (8, 44), and their numbers correlate with disease severity and progression (5, 8, 42, 43, 4548). The molecular mechanisms governing the TEM of this pathogenic subset into the CNS are poorly understood.…”
Section: Resultsmentioning
confidence: 99%
“…However, similar to MS, RR-EAE is also characterized by extensive CNS perivascular infiltration of inflammatory APCs that perpetuate damage (3, 8, 43). In particular, iDCs are major players in CNS autoimmune pathology (8, 44), and their numbers correlate with disease severity and progression (5, 8, 42, 43, 4548). The molecular mechanisms governing the TEM of this pathogenic subset into the CNS are poorly understood.…”
Section: Resultsmentioning
confidence: 99%
“…For example, studies have shown that the restimulation of tissue-resident antigen specific T cells was dependent upon the composition of the pro-inflammatory microenvironment, to include the expression of distinct molecules by the DCs (44,45). In another study, Clarkson et al demonstrated a role for DCs in expanding antigen specific T cells in the central nervous system; however, this was dependent on the expression of the chemokine receptor CCR2 by the DCs (46). Nevertheless, these data should be cautiously interpreted since a number of DC-associated factors can shape the outcome of the immune response, to include not only immune activation, but also tolerance (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Antigen-presenting cells (APCs) that reside within the choroid plexus and meninges express major histocompatibility complex class II and the C-type lectin receptor DNGR-1, also known as CLEC9A 31 , a marker of dendritic cell subsets with functional similarity to lymphoid and tissue dendritic cells. These resident APCs provide a mechanism for local restimulation of infiltrating T cells, which is required for their extravasation into the CNS parenchyma 32,33 . High concentrations of proinflammatory cytokines within the CSF of patients with infectious meningitis are associated with impaired cognition and correlate with poor outcome 34,35 .…”
Section: Cns Anatomy Dictates Immune Responses To Invading Pathogensmentioning
confidence: 99%